The Relationship Between Postpartum Mothers' Knowledge of Perineal Wound Care and Wound Healing Speed - Putri, Maidina; Hariati, Andi (International Journal of Health Sciences, 2025)
Background:Perineal wounds in postpartum mothers are a common condition following vaginal delivery that requires optimal care to prevent infection and promote healing. The mother's knowledge of perineal wound care is believed to play a crucial role in accelerating the healing process. Objective:To determine the relationship between postpartum mothers' knowledge about perineal wound care and the speed of wound healing. Method:This study used a cross-sectional design with 50 postpartum mothers as respondents at Community Health Center X. Knowledge was measured using a standardized questionnaire, while wound healing speed was assessed using the REEDA Scale on the 7th day postpartum. Data analysis was performed using the Chi-square test at a significance level of 0.05. Results:Of the 50 respondents, 32 mothers (64%) had good knowledge and 28 of them (87.5%) experienced rapid healing. The Chi-square test results showed a p-value of 0.002 (<0.05), indicating a significant relationship between postpartum mothers' knowledge and the speed of perineal wound healing. Conclusion:Good knowledge of postpartum mothers about perineal wound care is significantly related to accelerated wound healing.